Glacitectonic Deformation in Sediment and Bedrock, Hat Creek, British Columbia - Broster, Bruce (Géographie physique et Quaternaire, 1991)
ABSTRACTA variety of deformation structures attributed to glacial overriding occur in rock and sediment of an intermontane valley at Hat Creek, British Columbia. Sediments exposed in vertical outcrops along Hat Creek, display contrasting styles of deformation involving fluidization, as well as brittle and ductile deformations that appear to have been formed concurrently. Typical structures include: joints, faults, infillings, and clastic dikes comprising; fluid-escape structures, glacigenic injections, as well as fluidal and viscous hydraulic expulsions. A model is presented for the glacitectonic formation of hydraulic expulsions during compression of underlying partially saturated unfrozen sediments. Bedrock exposed in excavations at higher elevations displays joints, faults and wedge fillings possibly associated with subglacial freezing during glacial advance. Orientation of the structures are correlative with directions of glacier flow as inferred from fabric, striae and geomorphology. The structures are believed to have been the product of several interrelated factors, including: glacial dynamics, engineering properties of the glacier bed material, subglacial relief, and the variation between coalescing glaciers. Correlation with directions of glacial movement, association with glacial faciès and infilling by glacial sediments, are conditions considered to be glacigenic signatures useful in differentiation of glacial from nonglacial (e.g. earthquake) origins for similar structures elsewhere.